Openness of digital images in art museums - Sum, Hedren Wai Yuan (2015)
Art museums, in general, play significant roles in education today. They are constantly opening up their collections for access in the digital world. However, as museums continue to face challenges, such as resources and copyright restrictions, this study sought to explore the concept of openness and investigate how open are they in providing access to their collections for educational purposes? Using the ‘4R activities’ framework by Wiley (2010), content analysis was conducted on the digital image databases and terms of use of the top 100 most visited art museums worldwide to determine their openness. The sample of the study was obtained from an annual survey published by ‘The Art Newspaper’ in April 2014. Among these 100 museums, 67 of them were found to have provided access to their digital images, but of differing degree of openness in terms of access to their digital images, and how museums communicated their openness to the users.